2003
DOI: 10.1128/jvi.77.10.5712-5720.2003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Infectious Retrovirus Concentration from Colony-Forming Assay with Quantitative Analysis

Abstract: The colony formation assay is the most commonly used titration method for defining the concentration of replication-incompetent murine leukemia virus-derived retroviral vectors. However, titer varies with target cell type and number, transduction time, and concentration of polycation (e.g., Polybrene). Moreover, because most of the viruses cannot encounter target cells due to Brownian motion, their short half-lives, and the requirement for target cell division for activity, the actual infectious retrovirus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…According to our model estimates, the initial infection rate, ␤ 0 , is higher in ramp-up plasma recipient animals than in set-point plasma recipients in agreement with the findings that ramp-up plasma is more infectious than set-point plasma (26). The fact that 20 vRNA copies from ramp-up plasma could initiate infection is surprising given that prior studies have found that fewer than 0.1% of virions in plasma or culture media are infectious (5,22,30,42). However, a recent study (38) found that rapid dissociation of HIV-1 from cultured cells severely limits infectivity assays and masks the inherent high infectivity of virions.…”
Section: Discussionsupporting
confidence: 75%
“…According to our model estimates, the initial infection rate, ␤ 0 , is higher in ramp-up plasma recipient animals than in set-point plasma recipients in agreement with the findings that ramp-up plasma is more infectious than set-point plasma (26). The fact that 20 vRNA copies from ramp-up plasma could initiate infection is surprising given that prior studies have found that fewer than 0.1% of virions in plasma or culture media are infectious (5,22,30,42). However, a recent study (38) found that rapid dissociation of HIV-1 from cultured cells severely limits infectivity assays and masks the inherent high infectivity of virions.…”
Section: Discussionsupporting
confidence: 75%
“…This difference may mean that most particles (i) are defective and cannot complete the necessary infection steps or (ii) simply never come into contact with a permissive cell. Based on experimental observations of retrovirus properties and theoretical models using murine leukemia virus vectors, the second alternative is probably more likely (2,4,5,17,30,37). Further support for an underestimate of infectious particles comes from observations that titers can be increased by procedures such as the addition of polycations (46), vesicular stomatitis virus G (VSV-G) pseudotype formation (10,38), or spinoculation (38).…”
mentioning
confidence: 99%
“…Here, we have estimated the production rates of both infectious and non-infectious virus, allowing for a novel quantitative specification of the fraction of newly generated virus that is infectious. This fundamental quantity is important in understanding the role and influence of defective virus particles [48][49][50]52]; and, to our knowledge, this has not been measured before for any virus strain. We determined the theoretical minimum value for the proportion of infectious virions among newly produced virus, p, to be 8.62 × 10 -6 , by calculating the ratio of the infectious to total viral production rates k 50 / k. The ratio of the production rates, however, is actually p multiplied by a, where a is the conversion factor from RNA count of infectious virions to TCID 50 (i.e., roughly the fraction of infectious virions that are actually measured in a TCID 50 titration assay).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that retroviruses are predominantly defective, with less than 0.1% of virions in plasma or culture media being infectious [47][48][49]. On the other hand, it has recently been suggested that HIV-1 virions, for example, are inherently highly infectious, but that slow viral diffusion in liquid media and rapid dissociation of virions from cells severely limit infections in cultures (i.e., in assays measuring infectivity) [50,51].…”
Section: Discussionmentioning
confidence: 99%